Modelagem da qualidade de água no rio São Marcos, situado na bacia hidrográfica do Alto Paraná - Cunha, Barcelos Nathália (2019)
The main water conflicts in Brazil are directed in the arid regions, industrialized regions with high population density and regions with high demands for irrigation and hydroelectric potential simultaneously. These water problems have become more evident in the last decades, which led to the organizational and operational restructuring of public and private entities in this area of knowledge, with the consequent emergence of computational tools that act as a decision support system for hydrological resources on a hydrographic basin scale. With the focus on hydrographic basins that present conflicts between the agricultural and hydroelectric sectors, in addition to the need for quantitative water optimization, efficient management also needs to be assessed by the qualitative impacts caused by the progressive introduction of pesticides and fertilizers in the accumulation reservoirs. The water catchment area of the São Marcos river, located in upper Paraná between the states of Goiás and Minas Gerais and the Federal District, presents a water conflict of great relevance between the hydroelectric sector and the agricultural sector, aggravated in recent years by the cascade operations of power plants (potential of 52.5 MW) and Serra do Facão (potential of 210 MW), coupled with the growing demand for irrigation (total grant of 65.7 hm3 / month in 2018). The main objective of this master's study was to evaluate the maximum inflow of organic nitrogen, ammonia and total phosphorus that the Batalha and Serra do Facão accumulation reservoirs support to still comply with the limits defined in Conama Resolution 357: 2005. For this, a water quality model was first calibrated along the São Marcos river from the computational tool AQUATOOL, which includes the water quantity (SIMGES) and water quality (GESCAL) modules. The calibration of the model provided a good fit between the simulations and the measured data (for OD, BOD, organic nitrogen, ammonia, nitrate and total phosphorus) in 4 monitoring stations along the São Marcos river. By means of the factorial method, the sensitivity analysis ± 10% of the physical coefficients and calibrated biochemical reactions showed that only the natural aeration coefficients Ka, the degradation of carbonaceous organic matter kd, the conversion of ammonia to KNai nitrate and the rate of VSL sedimentation were sensitive, causing mean longitudinal variations of 20% for OD, 30% for BOD and 30% for nitrate. The sensitivity analysis of the water quality parameters initially estimated in all point and diffuse tributaries showed the importance of frequent monitoring of water quality, since the oscillation of ± 100% of the parameters caused an average variation of -3.65 % for OD, 26.85% for BOD, 16.37% for organic nitrogen, 22.17% for ammonia, 26.17% for nitrate and 15.65% for total phosphorus. Finally, in order to avoid the eutrophication process, in order to guarantee the water quality standards deliberated by CONAMA Resolution 357/2005 for class 2 in the lentic environment, the scenarios show a maximum capacity of 0.029 ton/km2.month of ammonia, 0.095 ton/km2.month nitrate and 2.09 kg/km2.month of total phosphorus in the battle reservoir contribution sub-basins and 0.19 ton/km2.month ammonia, 0.538 ton/km2.month of nitrate and 3.23 ton/km2.month for total phosphorus in the contribution sub-basins of Serra do Facão reservoir, all downstream of the Batalha reservoir. In general, the study contributes to the planning of land use and occupation in the São Marcos river basin.